2022
DOI: 10.5468/ogs.22063
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive continuous blood pressure monitoring using the ClearSight system for pregnant women at high risks of post-partum hemorrhage: comparison with invasive blood pressure monitoring during cesarean section

Abstract: ObjectiveThis study aimed to investigate the accuracy and precision of continuous, non-invasive blood pressure obtained using the ClearSight system by comparing it with invasive arterial blood pressure, and to assess the hemodynamic changes using invasive methods and the ClearSight system in patients undergoing cesarean section. MethodsArterial pressure was measured invasively with an intra-arterial catheter and non-invasively using the ClearSight system during cesarean section in patients with placenta previa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…only for MAP (participant BMI < 35 kg m À2 ). 17 agreement. 14 Our study fills a knowledge gap, evaluating the FC performance in pregnant women Class 3 obesity.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…only for MAP (participant BMI < 35 kg m À2 ). 17 agreement. 14 Our study fills a knowledge gap, evaluating the FC performance in pregnant women Class 3 obesity.…”
Section: Discussionmentioning
confidence: 75%
“…The acceptable proportion outside Zone A has not been defined in the cesarean delivery setting but is more likely to be <5%. Misugi et al, in the other study in pregnant patients comparing FC and INV, demonstrated adequate agreement only for MAP (participant BMI < 35 kg m −2 ) 17 . Frassanito et al, in a retrospective study (BMI < 35 kg m −2 ) compared only MAP readings from NIBP and FC during cesarean delivery, reporting good agreement 14 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite limited data, these noninvasive devices have shown potential for tracking responses to spinal anesthesia-induced sympathetic blockade and vasopressor administration without the need for invasive procedures in cesarean section [25][26][27]. For example, ClearSight™ (Edwards Lifesciences), a noninvasive continuous BP monitoring device using a finger cuff, has demonstrated acceptable accuracy and precision compared to that in invasive monitoring methods [28]. This device has been associated with a reduced incidence of hypotension and maternal nausea under spinal anesthesia [29].…”
Section: Noninvasive Continuous Blood Pressure Monitoringmentioning
confidence: 99%